对中国国有独资商业银行若干问题的探讨 = On the issues of state-owned commercial banks in China - 宋秋 Song, Qiu (2008)
Many State—Owned specialized Banks have converted into State—Owned Commercial Banks in China. During the process, many problems, such as property right assignment, monopolizing, inefficiency and bad loans have been observed. By analyzing fund structure, market structure and economic performance and their interaction of these banks, this paper identified these major problems: obscure property right, imperfect organization system and operation system.